2016
DOI: 10.3390/su8070601
|View full text |Cite
|
Sign up to set email alerts
|

Open Economy, Institutional Quality, and Environmental Performance: A Macroeconomic Approach

Abstract: Abstract:As the subject of how economic development affects the quality of the natural environment has gained great momentum, this paper focuses on examining the extent to which the openness of a market economy and the quality of the institution affect environmental performance. The majority of the current studies focus on the Environmental Kuznets Curve and the level of economic growth. This paper addresses this question by relating environmental ("Environmental Performance Index") to macroeconomic (Gross Dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 36 publications
7
34
0
1
Order By: Relevance
“…The purpose of EPIs is to provide a set of indicators, including how to collect and analyze them [60]. Various indicators are used to evaluate, improve and report performance for sustainability and environmental orientation [18,58,62,65]. In a study by Mazzi et al [62], EPIs in Italian local governments are described and the authors found great differences in what was measured.…”
Section: Environmental Performance Indicatorsmentioning
confidence: 99%
“…The purpose of EPIs is to provide a set of indicators, including how to collect and analyze them [60]. Various indicators are used to evaluate, improve and report performance for sustainability and environmental orientation [18,58,62,65]. In a study by Mazzi et al [62], EPIs in Italian local governments are described and the authors found great differences in what was measured.…”
Section: Environmental Performance Indicatorsmentioning
confidence: 99%
“…Therefore, green performance measures an enterprise in which business and environmental needs interact [42,43]. Achieving green performance requires enterprises not only to reduce pollution, waste and energy consumption, and improve customer safety [44,45] but also to survive and develop.…”
Section: Green Proactiveness Orientation and Green Performancementioning
confidence: 99%
“…Based on a content analysis of 533 Chinese listed companies, this study examines how corporate environmental performance affects not only the level of detail of a company's environmental disclosures but also what information is disclosed (Meng and Ashby, 2014). Mavragani et al (2016) focused on examining the extent to which the openness of a market economy and the quality of the institution affect environmental performance. The majority of the current studies focus on the Environmental Kuznets Curve and the level of economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For Mavragani et al (2016), by applying factor analysis, an empirical model of the Environmental Performance Index is estimated, suggesting that there is a significant positive correlation between a country's economic growth, the openness of an economy, high levels of effective governance, and its environmental performance.…”
Section: Literature Reviewmentioning
confidence: 99%